Ruta Turística de la parroquia Zamora, cantón Zamora, provincia de Zamora Chinchipe - Sarango Pinzón, Marjorie Judith (2018)
Ecuador is a country with an incomparable natural and cultural wealth. The diversity of its four regions has given rise to hundreds of thousands of species of flora and fauna. It has a diversity of peoples and nationalities that bring with them customs and traditions. In the southern Amazon region of Ecuador we find the Zamora parish belonging to the Zamora Canton in the province of Zamora Chinchipe, known nationally as the city of birds and waterfalls, as it has great natural and cultural wealth, with a wide variety of tourist attractions and a high degree of endemism in its flora and fauna. The Zamora parish has a great tourist wealth, which is why the development of this research work is important, plating as a general objective: Elaborate a "TOURIST ROUTE OF THE ZAMORA PARISH, CANTON ZAMORA, PROVINCE OF ZAMORA CHINCHIPE" - this objective includes everything related to the development of research work, where three specific objectives were set, the first objective; Carry out the tourist diagnosis of the Zamora Parish, Zamora Canton, Province of Zamora Chinchipe, the second objective.- Propose a Tourist Route for the Zamora Parish, Zamora Canton, Zamora Chinchipe Province and as third objective; Socialize the results of the research work with the actors involved in the project. In order to carry out the research, analytical, synthetic, inductive and deductive methods were used, together with the application of techniques such as direct observation, interview and MARPP technique, which allowed us to fully comply with the objectives set for the Development of the first objective through the use of the diagnostic matrix of Carla Ricaurte allowed obtaining valuable information on the tourist attractions through the inventory cards of the Ministry of Tourism (MINTUR), as well as determining the strengths, opportunities, weaknesses and threats through the SWOT matrix, for the development of the second objective taking into account the information obtained in the first objective, the synthetic method was used where GPS was used to obtain the geo-reference data of the points to trace the tourist route, where the design was determined by the brand and the name called "TOURIST ROUTE ZA MORA CAMINO TOWARDS NATURE ", likewise signage was designed based on the signaling manual of the Ministry of Tourism of Ecuador and promotion and marketing strategies were established for the diffusion of the route. For the fulfillment of the third objective the deductive method was used, as well as the MARPP techniques (Rapid Analysis Method and Participatory Planning) which consists of three phases; the first is the call made through an office addressed to Ing. Angel Mendoza of the tourism department of GAD Zamora, requesting date for socialization; In the second phase, the results of the research work obtained on the development of the Zamora Tourist Route on the way to nature were presented, finally in the third 11 phase the observations were raised, where the conclusions and recommendations in the research work were obtained. As conclusions, it was determined that the Zamora Parish possesses great tourist potential thanks to the great variety of waterfalls, diversity of flora and fauna which allows that new alternatives of tourist development are developed. The tourist route Zamora way to nature, is a new product that allows the promotion of tourist attractions driven the tourist and economic development of the parish Zamora. Finally, it is recommended to the GAD tourism department, so that in conjunction with the MINTUR training is carried out to staff of tourism service providers for their improvement, likewise so that more promotion and dissemination of the tourist attractions of Zamora is carried out on the other hand GAD Zamora is recommended, which takes into account the research work, thus improving tourism development, positioning the parish as a tourist destination of Zamora Canton and Province of Zamora Chinchipe.